Blended Learning Models: A Necessity for Modern Education - Aryal, Umesh (International Research Journal of MMC, 2025)
The research article explores the necessity of blended learning models to enhance more active engagement of students and their better academic performance. Using an exploratory research design, the study collected qualitative secondary data from books and journal articles. Qualitative descriptive analysis was executed to draw the findings. The findings reveal that blended learning models are necessary for modern education as they enhance flexibility, improve academic outcomes, boost student engagement, foster active learning, promote digital literacy, develop 21st-century skills, ensure accessibility and inclusivity, support educational continuity, encourage innovation in teaching, require professional development, promote inclusivity, and prepare students for the future. The study highlights the importance of integrating face-to-face and digital learning to enhance flexibility, engagement, academic outcomes, and inclusivity. Students, teachers, policy makers, and institutions will be benefitted from this study to prepare learners with 21st-century skills and digital literacy.